Perceiving the Suitability of Adopting Problem Based Learning Pedagogy for Technical Education Entrants - Dabir, Vaishnavi; Kulkarni, Anjali; Khare, Kanchan (Journal of Engineering Education Transformations, 2022)
During campus Interviews, the student's cognition is the Employers desideratum. They have incertitude regarding the same due to the scholastic system which is exam-oriented. It thus is an obligation on the teacher's part to ascertain that students get more proactive during the classroom sessions. Problem-based learning (PBL) could be an effective alternative tool for boosting their interest and involvement in technical education. As Symbiosis Institute of Technology is an autonomous body, the freedom of adopting a different teaching method was used. In this study, the first week of the academic semester was converted into a week full of PBL activities instead of regular classes on a cohort of students from diverse background. This was done to understand if students could apply pre-requisite knowledge that they gained through regular tutelage. To test the usefulness of the concept of PBL in technical education, few activities were planned to introduce students to new concepts allied with the course structure of that semester. The study showed that students had limitations in the application of prerequisite knowledge and 10% could solve the problem completely. 62% of students were successful in doing new tasks using the PBL technique. 8% of students were able to reach to correct solution. Thus, student engagement can be boosted by the use of PBL pedagogy in technical education.